Nitrogen Fertilization of Grass Leys: Yield Production and Risk of Nitrogen Leaching - Elena Valkama; Katri Rankinen; Perttu Virkajärvi; Tapio Salo; Petri Kapuinen; Eila Turtola (Сельскохозяйственные машины и технологии, 2019)
Abstract. The soil surface balance of nitrogen (N), calculated as the difference between N inputs and output, is a principal agri-environmental indicator that provides information on the potential loss of N to surface or groundwater. (Research purpose) Determination of relevant models of yield response to N fertilization could prove helpful in minimizing N balance and simultaneously maintaining high-yield production. (Materials and methods) The authors used meta-analysis to quantitatively summarize 40 N fertilization experiments on perennial grass leys in Finland and assessed the effect of inorganic N fertilization on grass yields and N balances, and further estimated potential to reduce N input and N balances. The relationship was estimated by using the COUP model (a coupled heat and mass transfer model for ‘soilplant-atmosphere’ systems) and by reviewing the 12 Nordic studies on N leaching experiments involving lysimeters and drained field plots. (Results and discussion) It was found that the optimal N content in mineral soils is 230 kilograms per hectare, in organic – 190. In the first case, the economic effect of nitrogen introduction is 206 euro per hectare, in the second one – 62. (Conclusions) The developed yield response models can serve to construct a dynamic tool for growers to adjust N applications for maximizing economic profitability. The authors proved that the values predicted by the COUP model for N leaching losses after the application of mineral N fertilizer to perennial grass leys were in accordance with the low values measured, which ranged from 1.2 to 10-15 kilograms per hectar a year in Finland and in the Nordic-Baltic countries. It was also revealed that a possible risk of N leaching losses when using only inorganic N fertilization seems less crucial due to its low level and weak association with N balances.